A photometric study of NSVS 7453183: a probable quadruple system with long-term surface activity. Issue 1 (9th January 2023) - Šmelcer, L; Wolf, M; Kučáková, H; Zasche, P; Kára, J; Hornoch, K; Zejda, M; Auer, R F
ABSTRACT: The VRC light curves were regularly measured for the eclipsing binary NSVS 7453183 as a part of our long-term observational project for studying of low-mass eclipsing binaries with a short orbital period and surface activity. The TESS light curve solution in phoebe results to the detached configuration, where the temperature of primary component was adopted to T 1 = 4300 K according to the SED approximation. It gives us T 2 = 4080 ± 100 K for the secondary component. The spectral type of the primary component was estimated to be K6, and the photometric mass ratio was derived q = 0.86. We confirm presence of the third body in this system, a stellar companion with a minimal mass 0.33 M⊙ orbiting the eclipsing pair with a short period about 425 days, and propose the next, fourth body with a longer orbiting period of about 12 years, probably a brown dwarf with the minimal mass of 50 MJup . The hierarchical structure ((1+1)+1) + 1 of this quadruple system is assumed. Characteristics and temporal variations of the dark region on the surface of the primary component were estimated. The average migration speed of about 10° per month was found during years 2020–2022.